Ocultação de paternidade ou filiação ilegítima? O lugar do galego na origem da língua portuguesa em textos dos séculos XVI e XIX - Passerini, Thiago Zilio (2019)
This paper has as theme the origin of Portuguese and is situated in the research line History and Portuguese language description. The general purpose is analyze the referred origin, considering the factors that lead to the erasure and resurgence of the Galician in texts from sixteenth and nineteenth century. The temporal cut proposed corresponds to two moments of great emphasis: the first relates to the apogee of the Lusitanian overseas empire and in the linguistic point of view, it inaugurates the grammatization process of the vernacular. The second links to the European state’s formation, in an emergency context of the nationalist ideals and with regard to the linguistic conceptions, mark the appearance of the comparative-historical method that, in Portugal, promoted the revisiting of the Cancioneiros, seriously marks of the Portuguese’s past, whose language started to be called Galician-Portuguese. The undertaken exam was based in the analyze of two corpora: one from sixteenth century that comprehend the Grammmatica da lingoagem portuguesa by Fernão de Oliveira and the Cartinha com os mandamentos da santa madre igreja, a Grammatica da lingua portuguesa e o Diálogo em louvor da nossa linguagem, by João de Barros. The nineteenth century embrace three articles published in books and periodical of the age, signed by Leite de Vasconcelos, Adolfo Coelho and Carolina Michaëlis de Vasconcellos. The analyze basis used was based in the methodological-theoretical principles proposed by Swiggers (2009; 2010) and Koerner (2014 [1974; 1987; 1993; 1994; 1995]). Among the specifics purposes figure: the promotion of one discussion of new theories able to change the current paradigm of the Portuguese history; the expansion of the discussions between the distinct spaces of Portuguese-speaking, including in them the Galician; the dissemination of the relevance of the linguistic historiography for these studies; and finally, the supply of material for the promotion of new researches related to these questions. In general, the results point to a close connection between the zeitgeist and the linguistic knowledge produced, so the process of erasure and resurgence of the Galician in the origin of the language told in the two centuries in question are fully explainable and conceivable when it considers the context that such knowledge was produced